INDUCTION OF LATE ABORTION WITH VAGINAL MISOPROSTOL: EXPERIENCE FROM NIGERIA - Oliver C, Ezechi; Olabisi M, Loto; Evangeline N, Amadi; Chikezie A, Nwokoro; Hakeem, Akinlade (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the outcome of induction of late abortion with vaginal misoprostol. Material and Methods: This prospective study of misoprostol induced late abortion at gestational age of 13-27 weeks was conducted in 3 Lagos hospitals. Following a decision to induce, 200mcg of Misoprostol was inserted into the posterior fornix and repeated 12 hourly until expulsion of the fetus. Statistical analysis was performed using SPSS for windows version 7.0. Results: Out of 102 patients, induction of late abortion was done mainly for fetal abnormalities (n=40, 39.2%) and intrauterine death (n=35, 34.3%). The age of the women ranged from 21 to 39 years. The modal gestational age was 15 weeks with a range of 13 to 27 weeks. Majority of the patients were multiparae (65.7%). The dose required to achieve expulsion ranged from 200 to 1000mcg with a mean of 364.7±102.4mcg.The mean induction expulsion interval (IEI) was 16±4 hours and 78.4% (80/102) expelled within 24 hours. The multiparous patients and cases of fetal deaths were associated with significantly shorter IEI. Gestational age more than 23 weeks was associated with fewer retained product rate Linear logistic regression analysis shows that multiparity (p<0.01), advanced gestation age (p=0.00) and fetal status (p<0.01) had independent association with IEI. Complete abortion rate was independently associated with gestational age (p<0.001) but not with parity and fetal status. Conclusion: Vaginal misoprostol alone is a safe and effective method of late abortion termination in areas were mifepristone is not available.